2018
DOI: 10.1209/0295-5075/124/24002
|View full text |Cite
|
Sign up to set email alerts
|

Shear-induced diffusion in non-local granular flows

Abstract: We investigate the properties of self-diffusion in heterogeneous dense granular flows involving a gradient of stress and inertial number. The study is based on simulated plane shear with gravity and Poiseuille flows, in which non-local effects induce some creep flow in zones where stresses are below the yield. Results show that shear-induced diffusion is qualitatively different in zones above and below the yield. Below the yield, diffusivity is no longer governed by velocity fluctuations, and we evidenced a di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 31 publications
1
19
1
Order By: Relevance
“…1(c), the evolution of normalized velocity fluctuations Δ with inertial number I strongly resembles that of the friction coefficient μ. For I > I t , all data points collapse on a single power law: Δ ∼ I 1=2 , consistent with previous studies [3,4,6]. On the contrary, for I < I t , no one-to-one relationship exists between Δ and I, but data points obtained for different values of Ω nevertheless follow parallel trends.…”
supporting
confidence: 89%
See 2 more Smart Citations
“…1(c), the evolution of normalized velocity fluctuations Δ with inertial number I strongly resembles that of the friction coefficient μ. For I > I t , all data points collapse on a single power law: Δ ∼ I 1=2 , consistent with previous studies [3,4,6]. On the contrary, for I < I t , no one-to-one relationship exists between Δ and I, but data points obtained for different values of Ω nevertheless follow parallel trends.…”
supporting
confidence: 89%
“…Numerous studies have, however, revealed the existence of nonlocal effects and deviations from purely rateindependent behavior in the quasistatic regime. In particular, creep as well as strong intermittent velocity fluctuations have been evidenced in quasistatic regions coexisting with inertial layers for different geometrical settings [4,[6][7][8][9][10][11].…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Motivated by these shortcomings, non-local rheology theories aim to capture relationships between the stress tensorσ and state variables in addition to the shear rateγ. Three Several such models have been proposed 7,[22][23][24][25][26] , but for the moment there still lacks a universal theory that captures the fundamental physics behind the vast variety of non-local phenomena 27,28 , and that is moreover well-posed 29,30 . In this work we focus on a particular cluster of models based on measures that are accessible to us.…”
Section: Introductionmentioning
confidence: 99%
“…This scaling is verified in diluted granular flows, where the grains' trajectory indeed involves a series of free, ballistic flights interrupted by a binary collision with another grain. However, deviations from that scaling were observed in dense granular flows of cohesionless and cohesive grains [8][9][10]. A qualitative way to understand the origin of these deviations is that grains interact via multiple and sustained contacts in dense granular flows.…”
Section: Introductionmentioning
confidence: 99%